2020
DOI: 10.3390/su12229622
|View full text |Cite
|
Sign up to set email alerts
|

Current Sustainable Trends of Using Waste Materials in Concrete—A Decade Review

Abstract: Concrete is the most used construction material in the world. Consequently, the mass extraction of virgin materials required for concrete production causes major environmental impacts. With a focus on promoting sustainability, numerous research studies on incorporating waste materials to replace virgin substances in concrete were undertaken. Despite this vast volume of published literature, systematic research studies on these sustainable concrete mixes that inform various stakeholders on current research tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 363 publications
(254 reference statements)
0
44
0
Order By: Relevance
“…Interestingly, the global construction industry consumes an estimated 20 billion tons of concrete every year and this large annual production of concrete consequently leads to an equally large estimated consumption of component materials of about 15 billion tons of aggregates and 4.2 billion tons of cement (Tosic et al, 2017). Taking into account the huge volume of concrete produced annually, the concrete industry is unquestionably one of the ideal mediums for the economic and safe use of millions of post-consumer waste plastics (Sandanayake et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the global construction industry consumes an estimated 20 billion tons of concrete every year and this large annual production of concrete consequently leads to an equally large estimated consumption of component materials of about 15 billion tons of aggregates and 4.2 billion tons of cement (Tosic et al, 2017). Taking into account the huge volume of concrete produced annually, the concrete industry is unquestionably one of the ideal mediums for the economic and safe use of millions of post-consumer waste plastics (Sandanayake et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing concrete up-cycling in concrete appears like a consistent way to improve recycling. Sandanayake and colleagues [77] as well as the French national research project [78] showed that it is feasible, under certain conditions, in terms of techniques, costs, and regulation. However, reuse and recycling of C&D waste in the Paris region face strong constraints [13].…”
Section: Insights For Defining Circular Economy Strategies In the Paris Region Based On Materials Flow Analysismentioning
confidence: 99%
“…The first attempt to use alternative material to cement was in 1920, which suggested sulfur as a concrete compound binder [1][2][3].…”
Section: Iraqi Journal Of Industrial Research (Ijoir)mentioning
confidence: 99%
“…SC has revealed high resistance against harsh environments like acid and salt environments compared to traditional cement. Additionally, SC has several useful characteristics than traditional cement, such as compressive, tensile, and flexural strength, and exhibits low absorption and permeability for water [3], [7]- [9].…”
Section: Iraqi Journal Of Industrial Research (Ijoir)mentioning
confidence: 99%